2011
DOI: 10.3354/dao02405
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of parapoxvirus from a spotted seal Phoca largha in Japan

Abstract: A spotted seal Phoca largha with nodular and scab lesions on the whole body was brought to an aquarium in Nagoya, Japan. We extracted DNA from the lesions and used the polymerase chain reaction (PCR) method for detecting orthopoxvirus and parapoxvirus DNA. Parapoxvirus but not orthopoxvirus DNA was detected. The partial nucleotide sequence of the envelope gene was determined from the PCR product, and the sequence was seen to be closely related to 2 parapoxvirus strains from spotted seals in Alaska, showing 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…While some are species-specific, others can infect a broad species range [ 21 ]. Poxvirus has been identified in eight species of the superfamily Pinnipedia [ 22 ]: five belong to the family Phocidae [grey seal ( Halichoerus grypus ) [ 23 - 28 ], harbor seal ( Phoca vitulina ) [ 29 , 30 , 28 ], Mediterranean monk seal ( Monachus monachus ) [ 31 ], spotted seal ( Phoca largha ) [ 32 , 33 ] and Weddell seal ( Leptonychotes weddellii ) [ 34 ]], and three belong to the family Otariidae [California sea lion ( Zalophus californianus ) [ 28 ], Steller sea lion ( Eumetopias jubatus ) [ 35 , 32 ] and South American sea lion ( Otaria flavescens ) [ 36 ]]. Some of these pinniped poxviruses have zoonotic potential and can cause lesions in humans, mostly on the skin [ 23 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…While some are species-specific, others can infect a broad species range [ 21 ]. Poxvirus has been identified in eight species of the superfamily Pinnipedia [ 22 ]: five belong to the family Phocidae [grey seal ( Halichoerus grypus ) [ 23 - 28 ], harbor seal ( Phoca vitulina ) [ 29 , 30 , 28 ], Mediterranean monk seal ( Monachus monachus ) [ 31 ], spotted seal ( Phoca largha ) [ 32 , 33 ] and Weddell seal ( Leptonychotes weddellii ) [ 34 ]], and three belong to the family Otariidae [California sea lion ( Zalophus californianus ) [ 28 ], Steller sea lion ( Eumetopias jubatus ) [ 35 , 32 ] and South American sea lion ( Otaria flavescens ) [ 36 ]]. Some of these pinniped poxviruses have zoonotic potential and can cause lesions in humans, mostly on the skin [ 23 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…None of the marine mammals currently inhabiting the Port of Nagoya Public Aquarium showed positive reactions in either ELISA or WB assays, which implies a lack of exposure to new SPPV infections since the last reported infection ( 29 ). Additionally, in respect of seal PL1 (from which the positive plasma sample had been collected approximately 10 years previously), its current serum (as of 2020) was not reactive; this result indicated that production of anti-SPPV antibodies after infection wanes over time.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were collected from each animal twice, in 2019 and 2020. A female spotted seal (PL1) had previously been infected with SPPV in 2010 (29), and a plasma sample that was collected from this animal at approximately 75 days after the onset of clinical signs (hereafter referred as PL1-2010 plasma) was used to validate the ELISA. Western blotting (WB).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pinniped parapoxviruses are characterized in California sea lions, northern fur seals, harbour seals from the north Pacific ocean; ringed (Pusa hispida) and spotted seals (Phoca largha) from the Arctic; grey and harbour seals from the Atlantic; southern sea lions (Otaria byronia) from South America, Weddell seals from Antarctica; Mediterranean monk seals (Monachus monachus) and Baikal seals [137,[144][145][146][147][148][149][150][151]. A new species of poxvirus related to an orthopoxvirus was associated with raised, ulcerated cutaneous lesions in Steller sea lion (Eumetopias jubatus) pups [147,152].…”
Section: Poxvirusesmentioning
confidence: 99%